SISTEM PENDUKUNG KEPUTUSAN PENENTUAN POTENSI ANGIN UNTUK PEMBANGKIT LISTRIK TENAGA BAYU (PLTB) MENGGUNAKAN METODE FUZZY MAMDANI - Busro Akramul Umam; Miftahul Walid (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2020)
In order to assist the government in realizing the use of 23% of EBT in 2025, to support the direction of government policies and strategies to improve accessibility by providing electricity to remote islands and villages. so in this study, the researcher makes a decision support system for determining the potential of renewable energy, especially energy produced by wind for wind power plants, The method used in this research is the Mamdani Fuzzy Logic, a system consisting of 3 Input criteria, including wind speed, temperature and air pressure, and output is potential for wind energy, output is presented in the form of a percentage unit with a range of 0-100%. The research was conducted in Sumenep Regency, after processing with the Fuzzy Mamdani method, the value of wind potential was generated with the average of the total output data = 43.51%, the value of min = 31.27%, the max value = 49.87%.